Pengaruh Sertifikasi Kompetensi Terhadap Kinerja Nazhir Dan Partisipasi Dalam Gerakan Perwakafan - Hamidiyah, Emmy; Buchori, Nur S; Yulianto, Arief Rohman; Huda, Nurul; Tanjung, Hendri; Beik, Irfan Syauqi (Badan Wakaf Indonesia, 2022)
The LSP of the Indonesian Waqf Board has been carrying out nazhir competency training and certification since November 2, 2021. So it is necessary to research the impact of nazhir competency training and certification on participant performance and participation. The purpose of this study: 1. To find out that nazhir certification affects the performance of the management and development of waqf assets in nazir institutions; 2. To find out how the nazhir certificate involves the participation of non-nazir participants in the waqf movement; 3. To determine the value of increasing the management and development of waqf assets in nazhir institutions after participating in competency training and certification; 4. To find out the value of the distribution of benefits in Nazhir institutions has increased after participating in competency training and certification; and 5. To find out the competency-based deals ​​, this certification influences reporting through BWI e-reporting. Respondents in this study were participants in competency training and certification, both those who work as nazhir and non-nazhir. The data analysis method in this study is Partial Least Square (PLS). The study results show that nazhir competency certification has a positive and significant effect on nazhir performance and non-nazhir participation in the waqf movement. The element of the competency certification assessment that has a high score is the attitude element. The component of Nazhir's performance, which has a high value, is from increasing the collection of waqf, while from non-Nazhir's participation which has a high value, is participation in the form of disseminating information to relatives, friends, and the work environment. The results of this study imply that it is necessary to make changes in the assessment of nazhir competence so that elements of knowledge and skills can have the same value as attitude.